KEABSAHAN HIBAH TANAH UNTUK KEPASTIAN HUKUM (Studi Putusan Mahkamah Agung Nomor 652 K/Ag/2019) - Mia Sumiati; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2020)
The problem on this case is that a land heirs that stole the portion of the other heirs by forging to take the land deeds that belongs to their other relatives to be named as one of the heirs, Marwan Efendi, based on the Grant Deeds that is made in front of PPAT Ida Kesuma and then its ownership to be transferred to Marwan Efendi, without the Plaintiff I,II, and III knowing, and the Defendant VII never signed that sale & purchase deeds, so in this case Marwan Efendi and PPAT Ida Kesuma had committed document falsification and signature to transfer the land rights through the Grant Deeds that’s inside (Study Towards Supreme Court Decision Number 652 K/ag/2019). Writer had done research on the case using Normative Legal Research Methods. Research data shows that there is an alliance between Marwan Efendi and PPAT Ida Kesuma whereas Meydalena (Defendant VII) never signed the SPD (Sale & Purchasing Deeds) between him/her and Marwan Efendi then has been cleared that in his excuse that he already give money and cars to the each Plaintiffs that is the heirs to the land, so in this case clearly against rule stated in article 1670 of KUHPerdata. By looking at the case it is better for someone to check the origin of the land so that nobody would suffer from it.